Use of wild edible and nutraceutical plants in Raya-Azebo District of Tigray Region, northern Ethiopia - Mirutse Giday; Tilahun Teklehaymanot (Tropical Medicine and Health, 2023)
Abstract Background Although there is a wide use of wild edible plants (WEPs) in Ethiopia, very little work has so far been done, particularly, in the Tigray Region, northern Ethiopia, to properly document the associated knowledge. The purpose of this study was, therefore, to document knowledge and analyze data related to the use of wild edible and nutraceutical plants in Raya-Azebo District of Tigray Region. The district was prioritized for the study to avoid the further loss of local knowledge and discontinuation of the associated practices because of the depletion of wild edible plants in the area mainly due to agricultural expansion and largely by private investors. Methods A cross-sectional ethnobotanical study was carried out in the study District to collect data through individual interviews held with purposively selected informants, observation, market surveys, and ranking exercises. Descriptive and inferential statistical methods were employed to analyze and summarize the data using Statistical Package for Social Sciences (SPSS) version 16. Results The study documented 59 WEPs, the majority of which (57.63%) were sought for their fruits. Most of the WEPs (49 species) were consumed in the autumn, locally called qewei, which includes the months of September, October, and November. Ziziphus spina-christi L. Desf., Balanites aegyptiaca (L.) Del. and Opuntia ficus-indica (L.) Miller were the most preferred WEPs. Both interviews and local market surveys revealed the marketability of Opuntia ficus-indica, Ziziphus spina-christi, Ficus vasta Forssk., Ficus sur Forssk., and Balanites aegyptiaca. Of the total WEPs, 21 were reported to have medicinal (nutraceutical) values, of which Balanites aegyptiaca and Acacia etbaica scored the highest rank order priority (ROP) values for their uses to treat anthrax and skin infections, respectively. Conclusions The current investigation demonstrated the wide use of WEPs in the district. In future nutritional composition analysis studies, priority should be given to the most popular WEPs, and nutraceutical plants with the highest ROP values.